Analisis Prioritas Upgrading Untuk Rekomendasi Peningkatan Kinerja Sistim Manufaktur Secara Berkelanjutan - Budiarto, Slamet; Suparno, S; Sudarso, Indung (Department Industrial Engineering, University of Muhammadiyah Malang, 2012)
The analysis is done by upgrading the priority, first create a model of activity with IDEF0 (Integrated Definition Language 0) To The Smallest activity. Verification is done by field officers, while the validation is done by software IDEF37. With regard that the activities that the model is a map of the activity. Then the next step don is weighting the importance of existing activities. Once the performance indicators of each activity is determined, then the analysis is then performed through the sorting and defining the activity of ICOM’s critical to determine which will be upgraded. Of data and processing is done, there are 627 ICOM’s are analyzed on the basis of performance indicators on a specific output. And consists of 15 stages are recommended for improved performance, assuming a single phase which comprises 30 ICOM’s performance will be improved within six months. The priority of upgrading is begined to upgrade technical specifications, human resources, and facilities at the activities planned production program. However, in general the activity plan programs and activities planned production capacity and desired material is the activity that most often experience upgrading in the first stage. Continuous performance improvement can be made with reference to the upgrading priority of phase II, III and so on. Evaluation upgrading needs to be done after the implementation of upgrading stage 3. It is useful to decide whether to do the upgrading stage IV or re-analyze priority.